The Analysis of Birth Rate in European Union by Means of Fourier Development - Ioan, Gina (Acta Universitatis Danubius. Œconomica, 2022)
In this article, it will carry out an analysis on the regularity of the indicator of all European Union countries. The research method consists in adjusting the statistical data with the help of Fourier series development and determining the periodicity of the phenomenon. Determining the possible periodicity facilitates the adjustment of the causes that lead to cyclization and therefore the mitigation of possible unwanted effects.